2023
DOI: 10.1002/ecs2.4396
|View full text |Cite
|
Sign up to set email alerts
|

Agroecological measures in meadows promote honey bee colony development and winter survival

Abstract: The homogenization of agricultural landscapes has led to a decrease in pollinator diversity and abundance. In response to this decline, farmers have implemented agroecological measures, which, in meadows, aim at providing more floral resources. These measures are the availability of unmown floral strips, delayed mowing, and discouraging the use of the conditioner, a device known to harm insects. The aim of our study was to investigate the cascade of effects of these agroecological measures on honey bee colony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Indeed, DeGrandi-Hoffman et al (2020) found that survival of fed colonies was higher than unfed colonies, despite fed colonies having higher Varroa populations and deformed wing virus levels. Furthermore, Hernandez et al (2023) demonstrated that increased forage quality led to higher populations of honey bees and consequently higher resistance in the population against Varroa . Future work should investigate these links, particularly the influence of landscape quality and supplemental feed on the ability of a colony to withstand Varroa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DeGrandi-Hoffman et al (2020) found that survival of fed colonies was higher than unfed colonies, despite fed colonies having higher Varroa populations and deformed wing virus levels. Furthermore, Hernandez et al (2023) demonstrated that increased forage quality led to higher populations of honey bees and consequently higher resistance in the population against Varroa . Future work should investigate these links, particularly the influence of landscape quality and supplemental feed on the ability of a colony to withstand Varroa .…”
Section: Discussionmentioning
confidence: 99%
“…Both Varroa infestation and lack of forage in the spring and summer reduce population size and small colonies struggle to thermoregulate and have lower overwintering success ( Owens 1971 ). Furthermore, poor nutrition disturbs honey bee colonies’ ability to withstand Varroa infestations; several studies describe a connection between protein supplemented diets, Varroa levels, and deformed wing virus (a virus vectored by Varroa mites) ( Janmaat and Winston 2000 , DeGrandi-Hoffman et al 2010 ) as well as between landscape quality and Varroa parasitization ( Dolezal et al 2019 , Hernandez et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%